The complexities of joy: a qualitative study of joy cultivation, loss of joy, and happiness in British adults - Maria Roberts; Richard Appiah (International Journal of Qualitative Studies on Health & Well-Being)
Introduction Joy is a fundamental yet underexplored emotion that plays a critical role in well-being and happiness. Despite its significance, little research has examined how individuals cultivate, experience, and lose joy, particularly in relation to its interplay with other emotions and broader aspects of well-being. This study explored the subjective and contextual dimensions of joy among UK adults, including how it is cultivated, lost, and related to the broader aspects of well-being. Methods Using an exploratory qualitative design, semi-structured interviews were conducted with 14 adults aged 28–59 years. Thematic analysis was employed to identify patterns in participants’ experiences of joy, its influences, and impact on well-being. Results Four key themes were constructed: The Dynamics of Joy in Everyday Life, Determinants of Joy: Influences and Barriers, Impact of Joylessness: Coping Behaviours, and Strategies for Cultivating Joy. Joy was perceived as a distinct, profound emotion, often intertwined with gratitude and love. Barriers to joy included negative relationships, societal pressures, and emotional burdens, whereas fostering positive relationships, engaging with nature, and cultivating self-awareness were identified as key strategies for sustaining joy. Discussion Findings highlight joy as a complex emotion, distinct from happiness and shaped by individual, relational, and cultural contexts. The study offers insight into joy’s emotional and psychological impact, the challenges of its loss, and the enduring value of joyful memories. Participants also shared practical suggestions for cultivating joy, which may inform well-being initiatives in community, educational, or therapeutic settings.